Correlation between Glycosylated Hemoglobin and Platelet Activity among patients with Type 2 Diabetes Mellitus - Ayesha Naz, Moiz Muhammad Shaikh, Asia Mazar, Aqsa Shaikh, Naila Masood, Imran Ali Shaikh (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Diabetes mellitus is globally increasing due to improper life style and non-healthy diet. The poor control of diabetes is attributed to various vascular complications and endothelial dysfunction. One of factors is increased thromboembolic events in small or large vessels. The poor control is also related to increased activity of platelets. The increased platelet activity is related to endothelial dysfunction. The mean platelet volume (MPV) is an indicator of the average size and activity of platelets. The increased HbA1c aggravates the MPV. Objective: To observe the association of glycosylated hemoglobin and mean platelet volume in type 2 diabetic patients. Study Design: Descriptive Cross sectional study Setting: Department of Medicine - Liaquat University of Medical & Health Sciences, Jamshoro, Hyderabad Duration of study: 06 months from June 29, 2022 to December 30, 2022. Methodology: Fifty-five patients with T2DM aged 18–60 years were consecutively enrolled. Demographic and clinical data were recorded. HbA1c and MPV levels were measured in the institutional laboratory. Data were analyzed using SPSS version 21. Pearson correlation coefficient was applied to determine the association between HbA1c and MPV. A p-value ≤0.05 was considered statistically significant Results: The mean age of participants was 43.47 ± 11.20 years. There were 28 (50.9%) males and 27 (49.1%) females. The mean BMI was 25.19 ± 5.42 kg/m². The mean HbA1c level was 6.92 ± 0.51%, and the mean MPV was 8.01 ± 0.85 fL. A weak but statistically significant positive correlation was observed between HbA1c and MPV (r = 0.281, p = 0.038). Conclusion: A statistically significant positive association was found between HbA1c and MPV in patients with T2DM. MPV may serve as a simple and cost-effective marker of platelet activity in diabetic patients. Keywords: Glycosylated Hemoglobin, Platelet activity, Diabetes Mellitus.